2010
DOI: 10.1590/s0103-64402010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's sarcoma of the mandible in a young child

Abstract: Ewing's sarcoma (ES) is a malignancy primarily affecting bone tissue that is commonly diagnosed in adolescents and young adults. Its occurrence in the head and neck region is unusual and generally involves the mandible and maxilla. An extensive review of the literature shows only few cases of the oral ES in patients under the age of 5. This paper reports a rare case of ES of the mandible in a 4-year-old girl, which had been previously misdiagnosed and treated as a dental abscess. In the clinical examination, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 19 publications
3
55
0
3
Order By: Relevance
“…20 The Mic-2 gene product (CD99) for all Ewing's Sarcoma family tumors with over 95% of the cases show positivity for this marker. 21 In our case, CD99 and NSE were identified to be positive.…”
Section: Discussionsupporting
confidence: 48%
“…20 The Mic-2 gene product (CD99) for all Ewing's Sarcoma family tumors with over 95% of the cases show positivity for this marker. 21 In our case, CD99 and NSE were identified to be positive.…”
Section: Discussionsupporting
confidence: 48%
“…Recently, it has been shown that high levels of CD133 expression in Ewing sarcoma cells are associated with chemoresistant Ewing sarcoma. 7 Therefore, CD133 could be a regarded as a marker for predicting which cases of Ewing sarcoma benefit more from preoperative chemotherapy and which cases benefit more from early surgical intervention. However, this is only a tentative suggestion requiring more intense experimentation to evaluate its usefulness in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…), CD31 and CD 34 (vascular tumors) Ki67 (breast cancer) synaptophysin (neuroblastoma) is also a diagnostic criteria for ES. 6 An additional translocation {t (11; 22) (q24; q12)} has been reported in other studies as a supportive data. Due to the non-availability, chromosomal analysis of bone marrow sample is not done in our study.…”
Section: Discussionmentioning
confidence: 55%
“…6 The diagnosis of ES is difficult due to its characteristic similarity with other malignant tumors. 7 A gradual increase of pain is one of the major symptoms of bone sarcomas.…”
Section: Discussionmentioning
confidence: 99%